CARREIRA NA MATERNIDADE: A percepção de mulheres de uma cidade no norte do estado do Rio Grande do Sul (Gestão & Regionalidade, 2022)
Previously, the challenge for women was just to enter the job market, today they need to overcome different obstacles to continue their careers after motherhood. In this context, the present study aimed to analyze the women's perception of career after motherhood. Through a qualitative research, fifteen interviews were conducted based on a semi-structured script with women working in private companies, which were analyzed through content analysis. The results showed that women have a traditional career perspective, but when they approach their trajectory they report a career without borders and protean. They also report that they felt the need to be able to have motherhood leave extended to six months as a major organizational benefit, as well as they need organizational policies that support this moment in their lives to reconcile career and motherhood.